Renewing Glances. Design and its Practice: Representing, Communicating, Narrating (diségno, 2017)
As ‘specialists’ or ‘public’, we are immersed daily in a world of images. This centrality of images has corresponded to a renewal in studies, theories, and methodologies of knowledge that can be derived and transmitted, especially for experiences connected to the means and forms of visualization. This is different in the discipline of drawing, however, which seems to have folded back on itself. About twenty years ago, it seemed that drawing could, or should, unfold over broad territories and that its practices participated in the construction of knowledge according to a system of specific means: heuristic, hermeneutic, referential ones.Today more than ever, the urgency for a new understanding of logic and illogic, truth and ethics, that is, scientific and aesthetic thou- ght, motivates the reflections and experiences proposed below. These reflections are useful in delineating the context of the need to renew the studies in drawing, along with its theories and methodologies, which can only originate through concrete practice. This is the perspective of the teaching experiences presented. These are experiences in which the exercise of drawing is an unavoidable mode due to the formation of a code of thought that can only be visual, and even more appropriately figural, because it is precisely in its writing that it acquires ‘body’ and ‘manner.’